Coronalexicon : meanings and word-formation processes of pandemic-related lexemes across English varieties - Gustilo, Leah-Espada; Pura, Cielo May; Biermeier, Thomas (Penerbit Universiti Kebangsaan Malaysia, 2021)
The rapidly-spreading infectious disease known as Covid-19 has created a global debacle which triggered the creation of a specialised language to reflect the new situations that have suddenly become part of people's lives. The goal of the present investigation is to describe the linguistic innovations that entered the lexicon of Englishes across the globe. This corpus-based study aimed at describing the meanings and word-formation processes of the trending pandemic-related revitalised and newly-formed compounds and blends in L1 and L2 English varieties. The findings of the current study have clearly displayed that the lasting effects of the pandemic are left indelibly in the lexical innovations introduced in language. Not all pandemic-related words will become permanent in the word stock of any given variety. However, given the long-lasting implications of COVID-19, documenting the nature of language upheaval during the pandemic and its contribution to the vocabulary of first and second language English varieties is of utmost importance.